OPTIMIZING THE ROLE OF PARENTS THROUGH LITERACY AND HEALTH AWARENESS IN SUPPORTING CHILD DEVELOPMENT - Azizah, Nurul; Indrawati, Tasya Juli; Arvisya O, Early; Hapsari P, Andaru (Antis-publisher, 2026)
Objective: The Community Service Program (KKN) in Balongdowo Village, Candi Sub-district, Sidoarjo Regency aimed to increase early childhood reading interest while strengthening parents’ role in supporting children’s growth and development. The background of this program was the low reading motivation among children, influenced by limited literacy facilities, health problems, and parents’ lack of awareness regarding the importance of early literacy. Method: The activities were carried out using a participatory approach through literacy workshops for parents, the establishment of a child-friendly reading corner, and basic health examinations to detect risks of stunting and malnutrition. KKN students collaborated with the local ‘Aisyiyah branch and TK/KB institutions in providing reading materials, conducting outreach, and mentoring children. Results: The program successfully established a reading corner with various attractive books for children, organized a literacy seminar that raised parents’ awareness, and implemented health checks that provided an overview of children’s growth conditions. Active participation of partners strengthened the program’s success, creating synergy among students, educational institutions, parents, and health cadres. Novelty: This KKN program offers an integrated model that combines literacy improvement and early childhood health monitoring simultaneously. Unlike conventional literacy programs, it provides a holistic impact by addressing both educational and health aspects while directly involving parents. This combined approach becomes the novelty that distinguishes the program from similar activities.